Enhancement of Electrochemical Performance of LiFePO(4)@C by Ga Coating - Yi, Dawei (ACS Omega, 2020)
[Image: see text] LiFePO(4) (LFP) is one of the cathode materials widely used in lithium ion batteries at present, but its electronic conductivity is still unsatisfactory, which will affect its electrochemical performance. Ga-coated LiFePO(4)@C (LFP@C) samples were prepared by a hydrothermal method and ultrasonic dispersion technology. Ga has good electrical conductivity and can rapidly conduct electrons within the LFP cathode material under the synergistic effect with C coating, thus improving the dynamic performance of the LFP cathode material. The experimental results show that LFP@C/Ga samples exhibit good electrochemical performance. Compared with the pristine LFP@C, the 1.0 wt % Ga-coated LFP@C cathode exhibits excellent discharge capacity and cycle stability. The former shows a discharge capacity of 152.6 mA h g(–1) at 1 C after 100 cycles and a discharge capacity retention rate of 98.77%, while pristine LFP@C shows only a discharge capacity of 114.5 mA h g(–1) and a capacity retention rate of 95.84% after 100 cycles at 1 C current density.